PERSEPSI GURU TERHADAP PERILAKU BELAJAR SISWA DI SMPN 26 MAKASSAR - Alimuddin, Ardawati; Arifin, Ibrahim (DISCOURSE: Indonesian Journal of Social Studies and Education, 2024)
This research aims to describe teachers’ perceptions of student learning behavior at SMPN 26 Makassar. This study used a qualitative descriptive approach by involving several teachers as respondents. Data were collected through semi-structured interviews and documentation to identify teachers’ views on student learning behavior. Data analysis was performed using data reduction, data display, and verification methods. The results of the study showed that the majority of teachers have a positive perception of student learning behavior. Teachers identified several positive behaviors that support learning, such as discipline, active involvement in discussions, and consistency in completing assignments. However, there were also some negative behaviors identified, such as the use of cellphones during lessons, tardiness, and lack of learning motivation. This research emphasizes the important role of teachers in shaping and directing student learning behavior. Teachers at SMPN 26 Makassar generally agree that appropriate interventions and innovative teaching strategies can improve student learning behavior. The recommendation from this research is the need for training for teachers to develop more effective classroom management techniques and improved communication between teachers, students, and parents. It’s can be concluded that teachers’ perceptions of student learning behavior greatly influence the teaching approach and the quality of learning in schools. This research provides valuable insights for the development of educational policies that support the formation of positive learning behaviors among students